FACTORS AND DIRECTIONS OF DEVELOPMENT OF PILGRIM TOURISM (Academicia Globe: Inderscience Research, 2023)
The article examines the development of pilgrim tourism, factors and opportunities that affect it. Various approaches to the definition of the concepts of religious tourism, pilgrim tourism, Islamic tourism are analyzed. The achievements in the development of pilgrim tourism in the country are analyzed and the tasks that need to be solved are highlighted.